Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1177/0194599813486257
|View full text |Cite
|
Sign up to set email alerts
|

Salvage Laryngectomy in Patients with Recurrent Laryngeal Cancer in the Setting of Nonoperative Treatment Failure

Abstract: Tumor staging, methods of initial and salvage treatment, and nodal disease were not significant predictors of survival. Both salvage partial and total laryngectomy were effective methods in the treatment of recurrent laryngeal cancer in carefully selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 16 publications
(23 reference statements)
6
48
1
1
Order By: Relevance
“…Van der Putten et al (12) also reported higher rates of complications following bilateral neck dissection in patients with neck dissection. In the study by Li et al (11), of the 72 early-stage patients, 15 (21%) patients without neck dissection had an improved survival compared to the 57 (79%) patients with neck dissection (P=0.042). By contrast, Wax and Touma (25) and Yao et al (26) recommended neck dissection in recurrent supraglottic carcinoma and advanced (rT3-T4) disease.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Van der Putten et al (12) also reported higher rates of complications following bilateral neck dissection in patients with neck dissection. In the study by Li et al (11), of the 72 early-stage patients, 15 (21%) patients without neck dissection had an improved survival compared to the 57 (79%) patients with neck dissection (P=0.042). By contrast, Wax and Touma (25) and Yao et al (26) recommended neck dissection in recurrent supraglottic carcinoma and advanced (rT3-T4) disease.…”
Section: Discussionmentioning
confidence: 93%
“…The optional management strategies for the primary tumor in recurrent laryngeal SCC are salvage surgery, including salvage total laryngectomy (STL), salvage partial laryngectomy (SPL) or endoscopic resection with a CO 2 laser (ERL), followed by re-irradiation with or without chemotherapy; supportive treatment and palliative chemotherapy are less effective options. Surgery is predominantly used for salvage in patients with recurrent laryngeal cancer following the failure of non-surgical treatments (radiation or chemoradiation) (10)(11)(12). ERL is only suitable for a small group of patients with early-stage disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While preserving function, partial laryngectomy affords no survival advantage. In a retrospective analysis of 56 patients with recurrent laryngeal cancer comparing total to partial laryngectomies, patient survival was not affected by the primary treatment or by salvage surgical approach, but was improved by obtaining negative margins [35]. Patients with an early disease relapse appear to have a worse prognosis compared with patients with a delayed relapse [36].…”
Section: Surgical Salvage Approachesmentioning
confidence: 99%
“…Laryngektomie pionowe, ze względu na szerokie stosowanie technik laserowych i gorsze wyniki funkcjonalne, są obecnie stosowane rzadziej [6,7]. Natomiast wiele technik resekcji poziomych, o różnym zakresie i miejscach zespolenia zyskało znaczenie zarówno jako leczenie pierwotne, jak i postępowanie ratujące [8][9][10][11][12][13][14].…”
Section: Wstępunclassified